Assessing the consequences of treatment with 131I on calcium, vitamin D3, parathormone, and cortisol in patients with thyroid abnormalities - Kourosh Bamdad; Raziyeh Khorramnejad (Fasa University of Medical Sciences, 2018)
Background & Objective: Consequences of radioisotope Iodine-131 therapy on tissues, organs, and blood parameters is a major concern in patients suffering from thyroid abnormalities that were treated with this classical treatment. Thus the aim of the present study is to assess the variations in the content of calcium, vitamin D3, parathyroid hormone, and cortisol in patients treated with radioiodine. Material & Methods: In two different stages, the first step before and then 48 hours after oral administration with radioactive iodine, venous blood from 132 cancerous thyroid female patients was analyzed. There was at least a two-month time gap between their thyroid surgery and the initiation of radioiodine therapy and it was the first time that patients were admitted for treatment with radioactive iodine. In this 48-hour period variations in calcium, vitamin D3, parathyroid hormone, and cortisol of the blood serum was measured. Each patient was compared to herself; however, the comparison of the entire community was also taken into considerations using statistical methods. Results: The results showed a significant decrease in levels of vitamin D3; after treatment with Iodine-131. Parathyroid hormone was also significantly reduced after 131I uptake; however, calcium levels remained almost unchanged. On the other hand, the cortisol level increased significantly. Conclusion: Increasing of cortisol levels; lowering the content of vitamin D3, and decreasing the amount of parathyroid hormone are consequences of treatment with 150 mCi Idine-131 in the understudied population.